Symptoms of acute stress, anxiety, and depression following Türkiye-Syria earthquake among Syrian population: national survey during the acute phase - Mhd Homam Safiah; Khaled Kalalib Al Ashabi; Mhd Obai Alchallah; Hani Alolabi; Sham Ataya; Youssef Latifeh (European Journal of Psychotraumatology)
Background: On 6 February 2023, an earthquake with a 7.8 magnitude wreaked destruction in northern Syria to add a new emergency status in the country. This study aims to evaluate the mental health status of the Syrian population in the immediate phase of the earthquake.Methods: This nationwide cross-sectional study was conducted in Syria from 17 February to 6 April. Data were collected on socio-demographics, trauma exposure characteristics, and levels of acute stress, depression, and anxiety. The NSESSS Checklist for the APA was used to assess ASD symptoms, PHQ-9 for depression, and GAD-7 for anxiety. Linear mixed-effects models were employed to identify predictive factors while accounting for governorate as a random effect and time elapsed as a fixed factor.Results: The rate of probable ASD symptoms was significant, with 55.3% of participants exhibiting these symptoms, including 10.3% reporting severe-to-extreme levels of severity. Similarly, 71.6% of participants exhibited symptoms of depression and 59.1% showed symptoms of anxiety. Furthermore, 40.4% of participants displayed a co-occurrence of ASD along with anxiety and depression. Linear mixed effects models indicated that symptoms were predicted by female sex, displacement, poor economic status, and a positive mental health history time elapsed, physical trauma, belief in the ongoing risk of earthquakes, feelings of dizziness, recurrent night-time fear arousal, and a continued sensation of seismic activity.Conclusion: This study demonstrated the high rates of symptoms of ASD, anxiety, and depression across the Syrian population during the immediate aftermath of the earthquake. High portions of people may acquire co-occurring symptoms represented by different mental health problems. These findings highlight the need for immediate actions to enhance mental health support in Syria.